The Role and Importance of Identity and Access Management in Firms - Ezhilarasan, Guhan Balaji; Svatá, Vlasta, 1952-; Zbořil, Martin; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2020)
This thesis intends to clarify how Identity and Access Management (IAM) controls can help the access management procedure used in firms by improving efficiency and reducing the threats related to mishandling of organization’s information and securing the access to organization’s data by providing authentication to right person to handle the information. Data security and Administrative factors influence the adequacy of IAM control systems. An ever increasing number of organizations are worry about their IT risks these days, particularly the organizations depending on IS (Information System) in business especially for access management. The goal of this thesis concentrated on what risks in the case company should be paid the most attention on priority to secure the information of the organization. Overall, the point is to assess the efficiency and reliably in digital identity handling and access approvals on the bases of IAM controls and the explanation. In addition, while investigating the risk management methodology; the benefits of the IAM controls in a firm is observed and reviewed with an example of how the control works in real world environment. The general strategy of this study is qualitative research technique. It intended to check if the general IT risks found in literature review and the data collected form case study to analysis on efficiency of identity and access management procedure.
Vedoucí práce: Vlasta Svatá
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: information systems management [obor dipl. práce]; diplomové práce; master's theses